logo

Ask Questions, Get Answers

 
X
 Search
Want to ask us a question? Click here
Browse Questions
Ad
0 votes

If $\cot\theta,cosec \theta$ are the roots of the equation $ax^2+bx+c=0$ and $\Delta=b^2-4ac$,then $a^4$ equals

$\begin{array}{1 1}(A)\;bc\Delta&(B)\;c\Delta\\(C)\;b^2\Delta&(D)\;b\Delta\end{array} $

Can you answer this question?
 
 

1 Answer

0 votes
$cosec\theta+\cot\theta=-\large\frac{b}{a}$
$cosec\theta\cot\theta=\large\frac{c}{a}$
$cosec^2\theta-\cot^2\theta=1$
$\Rightarrow cosec\theta-\cot\theta=-\large\frac{a}{b}$
$\Rightarrow cosec\theta=-\large\frac{1}{2}(\large\frac{b}{a}+\frac{a}{b})$
$\cot\theta=\large\frac{1}{2}(\large\frac{a}{b}-\frac{b}{a})$
Thus $-\large\frac{1}{4}(\frac{a^2}{b^2}-\frac{b^2}{a^2})=\frac{c}{a}$
$\Rightarrow a^4-b^4=-4acb^2$
$\Rightarrow a^4=b^4-4acb^2$
$\Rightarrow a^4=b^2(b^2-4ac)=b^2\Delta$
Hence (C) is the correct answer.
answered Apr 15, 2014 by sreemathi.v
 

Related questions

Ask Question
student study plans
x
JEE MAIN, CBSE, NEET Mobile and Tablet App
The ultimate mobile app to help you crack your examinations
Get the Android App
...